Racial inequalities in the educational context: an overview of the permanence of afro-brazilian people in schools (Research, Society and Development, 2022)
In this article, we sought, through a brief bibliographical research, to first know the historical context and, through this, to study and debate the social inequalities suffered by blacks in the educational context of schools in Brazil. There are statements that Brazil is a mixed-race country, because there are different peoples in its territory, thus having a mixture of races, and that everyone has the same rights, however, it is known that normally this does not happen, because, racial prejudice is rooted in society and is very present in the classroom. In this sense, it is necessary to address how racial prejudice affects the permanence of Afro-descendant students in schools, since data show that most students who give up attending classes are black. The methodology used was the qualitative approach together with the systematic literature review from scientific texts already published, among other works such as dissertations and theses on the proposed theme. Authors who theorize on the subject were used as theoretical support, among them: Cavelleir; Ferreira; Hüning; Lopes. It is concluded that the factors that contribute to school dropout of Afro-Brazilian students are not only linked to racial prejudice, there is an ideological creation established in contemporary society that attenuates these results.